2019
DOI: 10.1155/2019/3060658
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Hepatic Artery Embolization in Treating Solitary Fibrous Tumor Metastatic to the Liver

Abstract: The aim of this study was to evaluate safety and survival following hepatic artery embolization (HAE) for metastatic solitary fibrous tumor (SFT) in the liver. All patients with SFT metastatic to liver treated with HAE were retrospectively analyzed. Tumor response was evaluated using mRECIST. Objective response, overall survival (OS), and progression-free survival (PFS) were evaluated using Kaplan–Meier and multivariate Cox proportional hazard ratio. Adverse events were graded according to the National Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The best treatment for SFTs is complete resection of the tumor. Nevertheless, when curative resection is not available, metastasectomy, chemotherapy, and radiotherapy may be beneficial ( 18 , 19 ). A retrospective work ( n = 64) suggested that surgical resection of localized SFT can result in a 10-year overall survival (OS) of 58% when compared to that of metastatic SFT, which is 11% ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The best treatment for SFTs is complete resection of the tumor. Nevertheless, when curative resection is not available, metastasectomy, chemotherapy, and radiotherapy may be beneficial ( 18 , 19 ). A retrospective work ( n = 64) suggested that surgical resection of localized SFT can result in a 10-year overall survival (OS) of 58% when compared to that of metastatic SFT, which is 11% ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Velayati et al. summarized the safety and efficacy of the treatment of TACE ( 19 ). However, TACE may not always be effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been employed to effectively treat blood-rich tumors. Since a huge SFT usually has a large blood supply vessel, it has been reported that the blood loss during surgery was large ( 13 ), so preoperative selective embolization of the supply vessel of SFTs could reduce intraoperative blood loss without blood transfusion ( 30 , 31 ). In this study, seven patients received preoperative arterial embolization, and preoperative embolization was not found as a risk factor for postoperative complications in the risk factor analysis.…”
Section: Discussionmentioning
confidence: 99%